«This Long Ninth Century»: Yenisei Kyrgyz in the Usinsk Basin - Mitko Oleg A. (Поволжская археология, 2025)
The article is dedicated to the analysis of the issues of periodization and local variants of the Yenisei Kyrgyz culture in the Southern Siberia. The concept of the «long ninth century» is used in relation to the history and archaeology of the medieval population that occupied the Usinsk Basin in the Western Sayan Mountains after 840 AD. It is understood as the integrity of the key elements of the Usinsk Kyrgyz culture, its chronological continuity and inertia, which allowed maintaining the evolutionary nature of development for several centuries. By now, about 16 medieval archaeological sites have been excavated – campsites and burial and memorial complexes containing burials made according to the rite of cremation on the side. The topography of the large burial grounds of Mutnaya I and Eidiktyr-kyr has the same features as the monuments of the first variant of the Kyrgyz culture, located in Central Tuva and the Yenisei Canyon. Metal sets of horseman's and riding horse's equipment from cremation burials also form a single object complex. Only the ornamentation of ceramic vessels is unique. A hypothesis about the entry of the Usinsk Kyrgyz into one of the «six divisions» within the Kem-Kemdzhiut region and their creation of an independent social and political formation – the «Us region», known from written sources, has been put forward. The upper date for the end of the «long ninth century» – 1293 – is determined by the resettlement of the Usinsk Kyrgyz by the Mongols outside the Sayan-Altai Plateau.